Opłacalność faktoringu dla przedsiębiorstw na przykładzie FHU Transrol - Basiaga, Katarzyna (My University, 2012)
Purpose of this written work is researching of profitability of employment of factoring in FHU Company it does not use with factoring presently, however, it acts in sectors characterizing of Seasonal sale that causes problems with maintenance of financial liquidity. These problems are particularly painful in winter period, when it realizes Contract of winter maintenance of roads. Company owns credit in current account. However, conceded limit is scarce in winter period. Thus, it has been selected proper kind of factoring (factoring) in the present work on base of offer bank millennium for firm Transrol. Cost of factoring was compared with cost of boosts of credit limits in current account in co-operative bank in Krynica-Zdrój, where firm owns basic account. From processed analysis result , that for firm Transrol which acting in sectors characterizing seasonal sale and testifying for units of local governments services, self-governed factoring would be fairest kind of factoring. Analysis has showed that cost of self-governed factoring for FHU Transrol are comparable with cost of boosts of credits in current account. From the point of view of simplest access to self-governed factoring, it can be better solution than credit option for FHU Transrol.

Praca poświęcona jest badaniu opłacalności zastosowania faktoringu w FHU Transrol. Przedsiębiorstwo to obecnie nie korzysta z faktoringu, jednak działa w branżach, które dotyka sezonowość sprzedaży, co powoduje problemy z utrzymaniem płynności finansowej. Problemy te są szczególnie dotkliwe w okresie zimowym, kiedy to firma realizuje kontrakty na zimowe utrzymanie dróg. Przedsiębiorstwo posiada co prawda kredyt w rachunku bieżącym. Jednak w okresie zimowym przyznany limit jest niewystarczajacy. W związku z tym w niniejszej pracy na podstawie oferty faktoringowej Banku Millennium dobrany został dla Firmy Transrol odpowiedni rodzaj faktoringu, a jego koszty porównane z kosztami zwiększenia limitu kredytu w rachunku bieżącym w Banku Spółdzielczym w Krynicy – Zdroju, gdzie firma posiada konto podstawowe. Z opracowanej analizy wynika, że dla firmy Transrol działającej w branżach chrakteryzujących się sezonowością sprzedaży i świadczącej usługi dla jednostek samorządu terytorialnego najlepszym rodzajem faktoringu byłby faktoring samorządowy. Koszty tej usługi okazały się być dla omawianej firmy porównywalne z kosztami zwiększenia kredytu w rachunku bieżacym, a ze względu na łatwiejszy dostęp do tej usługi może on być lepszym rozwiązaniem dla firmy niż opcja kredytowa.
Profitability of factoring for enterprises on the example of FHU Transrol
Keywords: analiza finansowa przedsiębiorstwa; faktoring; faktoring a kredyt; faktoring samorządowy; kapitał obrotowy; rodzaje faktoringu; wierzytelności; zapotrzebowanie na kapitał obrotowy; financial analysis; factoring; factoring versus credit; self-governed factoring; circulating assets; kind of factoring; receivables; capital requirements rotary